PAKET PEMUPUKAN WORTEL PADA TANAH LEMPUNG LIAT BERPASIR DATARAN RENDAH DI PALANGKA RAYA - KALIMANTAN TENGAH - Firmansyah, Muhammad Anang; Rahayu, Wiwik; Liana, Twenty (BERITA BIOLOGI, 2018)
Carrot (Daucus carota L.) is generally cultivated at uplands areas. However, for lowlands, technology of innovation related to fertilizing can be considered as the solution. This study was aimed to determine the appropriate fertilizer package, the variety of carrot adapted in rainy season, and sandy clay loam of the lowland areas in Palangka Raya, Central Kalimantan. This study was designed by using a split plot exponential design consisting of main plot consisting of carrot varieties: (V1 = Kirana and V2 = Lokal Batu) and sub-plot, consisting of fertilizer packages (P0 = control, P1 = low. P2 = medium, P3 = High). The results showed that variety of Lokal Batu was more adaptive than Kirana for having higher tuber production. 16.95 g/plant (10.12 t/ha) and 16.33 g/plant (9.80 t/ha). The result showed that the highest production of 18.89 g/plant was obtained in a medium fertilizer package as compared to other fertilizer package. There was no significant interaction between carrot varieties and fertilizer packages. The trend showed that the fertilizer packages of P2 produced the highest yield of total weight of tuber production within each carrot variety of 10.36 ton/ha for Kirana and 12.31 ton/ha for Lokal Batu.